Pengaruh Struktur Aktiva, Ukuran Perusahaan, Operating Leverage dan Pertumbuhan Penjualan Terhadap Struktur Modal Pada Perusahaan Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia (2017-2020): Bahasa Indonesia - Deasy Arisandy Aruan; Putri Sitanggang; Catrin Naomi Lumban Tobing; Lasriana Harianja (Politeknik Ganesha Medan, 2022)
This study aims to determine the effect of asset structure, firm size, operating leverage and sales growth on capital structure of food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2017-2020. The data used is sourced from financial data on the Indonesia Stock Exchange through the website www.idx.co.id , and a selection has been made according to predetermined criteria. The population used in this study is Food and Beverage companies, totaling 30 companies, by using a purposive sample, the resulting sample is 17 companies. With this research, it is hoped that it can become a science to help further researchers as well as students or the general public who need a source of information. From the research, it can be seen that Asset Structure, Company Size, Operating Laverage and Sales Growth have a positive and significant effect simultaneously on profit growth. Asset structure and firm size have a negative and insignificant effect on profit growth. Operating leverage has a positive and significant effect on profit growth while Sales Growth has a positive but not significant effect on profit growth in food and beverage companies listed on the Indonesia Stock Exchange for the 2017-2020 period.